Negative active particle and preparation method thereof, negative pole piece, battery and electronic equipment

By alternately depositing silicon phosphorus particles and phosphorus particles in the carbon skeleton to form negative electrode active particles with high conductivity and stable structure, the problem of degradation of battery performance caused by expansion of silicon materials in lithium-ion batteries is solved, and a higher specific capacity and cycle retention rate is achieved.

CN119725422APending Publication Date: 2025-03-28GUANGDONG OPPO MOBILE TELECOMMUNICATIONS CORP LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311283415.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Silicon materials expand during the lithium embedding process of lithium-ion batteries, resulting in an accelerated electrolyte consumption and a decrease in circulation capacity retention.

Method used

The negative electrode active particles including carbon frameworks, silicon phosphorus particles and phosphorus particles are used to deposit these particles by alternately passing into the carbon frameworks of silicon source gas and phosphorus source gas to form a negative electrode material with high conductivity and stable structure.

Benefits of technology

The conductivity of the negative electrode active particles is improved, the polarization of lithium embedded and detachment is reduced, the lithium removal ability is enhanced, and the specific capacity and cycle retention rate are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725422A_ABST
    Figure CN119725422A_ABST
Patent Text Reader

Abstract

The invention provides a negative active particle and a preparation method thereof, a negative pole piece, a battery and electronic equipment. The negative electrode active particle provided by the embodiment of the invention comprises a carbon skeleton, wherein the carbon skeleton is provided with a plurality of pores; the silicon phosphorus particles are positioned in the plurality of pores; and a phosphorus particle located in the plurality of pores. The negative electrode active particle provided by the embodiment of the invention has relatively high conductivity and relatively high cycle capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronics, and in particular to a negative electrode active particle and a preparation method thereof, a negative electrode plate, a battery and an electronic device. Background Art

[0002] Silicon material has a high theoretical specific capacity (the theoretical specific capacity of silicon is 4200mAh / g) and is the most promising negative electrode material for the next generation of high energy density batteries. However, silicon itself will expand greatly during the lithium insertion process and repeatedly decompose to form a new solid electrolyte interface (SEI membrane) during the charge and discharge process, which will accelerate the consumption of the electrolyte and cause the battery's cycle capacity retention rate to drop too quickly. Summary of the invention

[0003] The embodiment of the present application provides a negative electrode active particle having higher electrical conductivity and higher cycle capacity retention rate.

[0004] The first embodiment of the present application provides a negative electrode active particle, which includes:

[0005] A carbon skeleton having a plurality of pores;

[0006] silicon-phosphorus particles, the silicon-phosphorus particles being located in the plurality of pores; and

[0007] Phosphorus particles are located in the plurality of pores.

[0008] A second aspect of the present application provides a method for preparing negative electrode active particles, which comprises:

[0009] providing a carbon skeleton having a plurality of pores; and

[0010] Silicon source gas and phosphorus source gas are alternately introduced into the carbon skeleton to deposit silicon-phosphorus particles and phosphorus particles in the plurality of pores to obtain negative electrode active particles, wherein the negative electrode active particles include a carbon skeleton, silicon-phosphorus particles and phosphorus particles.

[0011] The third aspect of the present application provides a negative electrode sheet, characterized in that it includes:

[0012] A negative electrode current collector; and

[0013] A negative electrode active layer is disposed on the surface of the negative electrode current collector, and the negative electrode active layer comprises the negative electrode active particles described in the first aspect of the present application or the negative electrode active particles prepared by the preparation method of the negative electrode active particles described in the second aspect of the present application.

[0014] A fourth aspect of the present application provides a battery, characterized in that it includes:

[0015] Electrolyte;

[0016] A positive electrode sheet, wherein the positive electrode sheet is at least partially immersed in the electrolyte;

[0017] a diaphragm, the diaphragm being located on one side of the positive electrode plate and at least partially immersed in the electrolyte, and

[0018] The negative electrode plate described in the third aspect of the present application is arranged on a side of the diaphragm away from the positive electrode plate and is at least partially immersed in the electrolyte.

[0019] A fifth aspect of the present application provides an electronic device, which includes: a device body; and

[0020] The battery described in the fourth aspect of the present application is used to power the device body.

[0021] In an embodiment of the present application, the negative electrode active particles include a carbon skeleton, silicon-phosphorus particles and phosphorus particles, the carbon skeleton having a plurality of pores, the silicon-phosphorus particles and the phosphorus particles are both located in the plurality of pores of the carbon skeleton, the distribution of phosphorus in silicon can provide more free electrons, increase the carrier concentration in the silicon phase, and thus improve the conductivity of the negative electrode active particles; the improvement in the conductivity of the negative electrode active particles will reduce the polarization of lithium embedding and extraction, can help lithium to be more fully extracted from the inside of the negative electrode active particles, help to reduce the lithium loss caused by insufficient silicon kinetic performance, and thereby improve the specific capacity and cycle retention rate of the negative electrode active particles. In addition, the presence of phosphorus particles can better isolate silicon-phosphorus particles. The presence of phosphorus in silicon-phosphorus particles can better prevent the growth of silicon-phosphorus particle size and reduce the size of connected silicon phases. The smaller silicon phase size allows the negative electrode active particles to effectively prevent the formation of Li15Si4 crystal phases when lithium is inserted, thereby reducing the volume change of the negative electrode active particles during the lithium insertion process, and better weakening the breakage of the negative electrode active particles caused by the formation of Li15Si4 crystal phases, so that the negative electrode active particles have a more stable silicon structure, thereby having a higher cycle capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 Schematic diagram of the structure of negative electrode active particles according to an embodiment of the present application.

[0024] Figure 2 It is a schematic diagram of the enlarged structure of a single pore of the negative electrode active particles according to an embodiment of the present application.

[0025] Figure 3 A schematic structural diagram of negative electrode active particles according to another embodiment of the present application.

[0026] Figure 4 It is a schematic diagram of a process for preparing negative electrode active particles according to an embodiment of the present application.

[0027] Figure 5 It is a schematic flow chart of a method for preparing negative electrode active particles according to another embodiment of the present application.

[0028] Figure 6 This is a scanning electron microscope image of the negative electrode active particles prepared in Example 1 of the present application.

[0029] Figure 7 This is an X-ray spectrometer diagram of the silicon element of the negative electrode active particles prepared in Example 1 of the present application.

[0030] Figure 8 This is an X-ray energy spectrometer diagram of the phosphorus element of the negative electrode active particles prepared in Example 1 of the present application.

[0031] Fig. 9 It is a schematic diagram of the structure of the negative electrode plate of one embodiment of the present application.

[0032] Fig.10 It is a schematic diagram of the structure of a battery according to an embodiment of the present application.

[0033] Fig.11 The battery of one embodiment of the present application is Fig.10 Schematic diagram of the cross-sectional structure in the AA direction.

[0034] Fig.12 It is a schematic diagram of the structure of the positive electrode plate of one embodiment of the present application.

[0035] Fig.13 It is a schematic diagram of the structure of an electronic device according to an embodiment of the present application.

[0036] Fig.14 It is a schematic diagram of the exploded structure of an electronic device according to an embodiment of the present application.

[0037] Fig.15 It is a circuit block diagram of an electronic device according to an embodiment of the present application.

[0038] Description of reference numerals:

[0039] 100-negative electrode active particles, 10-carbon skeleton, 11-pores, 30-silicon phosphorus particles, 50-phosphorus particles, 70-carbon coating, 400-negative electrode plate, 410-negative electrode current collector, 430-negative electrode active layer, 500-battery, 510-positive electrode plate, 511-positive electrode current collector, 513-positive electrode active layer, 530-diaphragm, 550-shell, 570-end cover assembly, 600-electronic device, 610-device body, 611-display screen, 613-middle frame, 615-shell, 6151-light-transmitting part, 616-memory, 617-processor, 618-camera module. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0041] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0042] The technical solutions in the embodiments of the present application will be described below in conjunction with the accompanying drawings.

[0043] It should be noted that, for the convenience of explanation, in the embodiments of the present application, the same figure marks represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.

[0044] With the continuous development of lithium-ion battery technology, lithium-ion batteries have the advantages of large specific capacity, no memory effect, high operating voltage, fast charging speed, wide operating temperature range, long cycle life, small size, light weight, etc. compared with other types of batteries such as lead-acid, cadmium nickel, etc. At present, lithium-ion has been widely used in mobile phones, laptops, electric vehicles, energy storage cabinets and other fields, and its application range is becoming more and more extensive.

[0045] Silicon material has a high theoretical specific capacity (the theoretical specific capacity of silicon is 4200mAh / g) and is the most promising negative electrode material for the next generation of high energy density batteries. However, silicon itself will expand greatly during the lithium insertion process and repeatedly decompose to form a new solid electrolyte interface (SEI membrane) during the charge and discharge process, which will accelerate the consumption of the electrolyte and cause the battery's cycle capacity retention rate to drop too quickly.

[0046] In order to solve the expansion problem of silicon during lithium insertion, silicon and carbon can be combined to form a silicon-carbon composite material, which can effectively alleviate the expansion problem of silicon during lithium insertion. However, the insufficient conductivity of silicon and carbon themselves has a certain impact on the electronic conduction of the silicon-carbon composite material, which increases the resistance to electron transmission. The material needs to combine or remove electrons when inserting or removing lithium. The deterioration of electron transmission will increase the polarization of the silicon-carbon composite material in this electrochemical process, making lithium precipitation more likely to occur, affecting the cycle performance of the battery. In addition, when depositing silicon, the silicon-carbon composite material tends to form larger silicon particles. Larger silicon particles are more likely to generate Li when inserting lithium. 15 Si4 crystal phase. During the formation of the crystal phase, the silicon-carbon composite material will cause higher internal stress and produce greater volume changes, which will deteriorate the cycle performance of the negative electrode material.

[0047] See also Figure 1 and Figure 2 An embodiment of the present application provides a negative electrode active particle 100, which includes a carbon skeleton 10, silicon-phosphorus particles 30 and phosphorus particles 50, wherein the carbon skeleton 10 has a plurality of pores 11; the silicon-phosphorus particles 30 are located in the plurality of pores 11; and the phosphorus particles 50 are located in the plurality of pores 11.

[0048] The negative electrode active particles 100 of the present application can be used in batteries (such as lithium batteries) as active materials of negative electrode plates of the batteries.

[0049] It should be noted that the carbon skeleton 10 has a plurality of pores 11 . It can be understood that the carbon skeleton 10 is a porous structure.

[0050] It can be understood that the silicon-phosphorus particles 30 include silicon and phosphorus. In the silicon-phosphorus particles 30 , the phosphorus is dispersed in the silicon.

[0051] It can be understood that in the plurality of pores 11 , the phosphorus particles 50 are interspersed between the silicon-phosphorus particles 30 .

[0052] It can be understood that the negative electrode active particles 100 of the present application are phosphorus-containing silicon-based negative electrode materials.

[0053] In an embodiment of the present application, the negative electrode active particles 100 include a carbon skeleton 10, silicon-phosphorus particles 30 and phosphorus particles 50. The carbon skeleton 10 has a plurality of pores 11. The silicon-phosphorus particles 30 and the phosphorus particles 50 are both located in the plurality of pores 11 of the carbon skeleton 10. The distribution of phosphorus in silicon can provide more free electrons, increase the carrier concentration in the silicon phase, and thus improve the conductivity of the negative electrode active particles 100. The improvement of the conductivity of the negative electrode active particles 100 will reduce the polarization of lithium insertion and extraction, and can help lithium to be more fully extracted from the inside of the negative electrode active particles 100, which helps to reduce the lithium loss caused by the insufficient kinetic performance of silicon, thereby improving the specific capacity and cycle retention rate of the negative electrode active particles 100. In addition, the presence of phosphorus particles 50 can better isolate the silicon-phosphorus particles 30. The presence of phosphorus in the silicon-phosphorus particles 30 can better prevent the size of the silicon-phosphorus particles 30 from growing, reduce the size of the connected silicon phase, and the smaller silicon phase size enables the negative electrode active particles 100 to effectively prevent Li from being inserted into the negative electrode active particles 100. 15 The formation of Si4 crystal phase can reduce the volume change of negative electrode active particles 100 during lithium insertion and better weaken the Li 15 The formation of the Si4 crystal phase causes the negative electrode active particles 100 to break, so that the negative electrode active particles 100 have a more stable silicon structure and thus have a higher cycle capacity retention rate.

[0054] In some embodiments, the specific surface area S' of the carbon skeleton 10 is in the range of 500 m 2 / g≤S'≤4000m 2 / g. Specifically, the specific surface area of ​​the carbon skeleton 10 may be, but is not limited to, 500m 2 / g, 600m 2 / g、800m 2 / g、1000m 2 / g、1500m 2 / g, 2000m 2 / g, 2500m 2 / g、3000m 2 / g、3500m 2 / g, 4000m 2 / g, etc. If the specific surface area of ​​the carbon skeleton 10 is too high, it means that there are a large number of pores 11 in the carbon skeleton 10, which makes the silicon content that can be deposited too high, and the silicon-phosphorus particles 30 in the same pore 11 are easily connected to form a continuous silicon phase of larger particles, resulting in excessive expansion of a single silicon-phosphorus particle 30 during lithium insertion; if the specific surface area of ​​the carbon skeleton 10 is too low, the content of deposited silicon is insufficient, which easily makes the specific capacity of the obtained negative electrode active particles 100 too low.

[0055] Furthermore, the specific surface area S' of the carbon skeleton 10 is in the range of 600 m 2 / g≤S'≤3000m 2 In this way, the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 can be better controlled, so that the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 is smaller, thereby having a better cycle capacity retention rate, and the negative electrode active particles 100 can have a higher specific capacity.

[0056] Furthermore, the specific surface area S' of the carbon skeleton 10 is in the range of 800 m 2 / g≤S'≤2000m 2 In this way, the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 can be better controlled, so that the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 is smaller, thereby having a better cycle capacity retention rate, and the negative electrode active particles 100 can have a higher specific capacity.

[0057] In some embodiments, the mass of phosphorus in the negative electrode active particles 100 is 0.1% to 25% of the mass of silicon. It can be understood that in the negative electrode active particles 100, the total mass of phosphorus in the silicon-phosphorus particles 30 and the phosphorus particles 50 is 0.1% to 25% of the mass of silicon in the silicon-phosphorus particles 30. Specifically, in the negative electrode active particles 100, the mass of phosphorus can be, but is not limited to, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 7%, 10%, 12%, 14%, 16%, 18%, 20%, 23%, 25% of the mass of silicon. In the negative electrode active particles 100, if the phosphorus content is too high, the silicon content is too low, which reduces the specific capacity of the negative electrode active particles 100 and is not conducive to improving the energy density of the battery using the negative electrode active particles 100; if the phosphorus content is too low, it is difficult to effectively prevent the growth of silicon size, which easily makes the size of the silicon phase too large, and it is easy to form Li during the lithium insertion process. 15 The Si4 crystal phase reduces the cycle capacity protection rate of the negative electrode active particles 100. When the mass of phosphorus in the negative electrode active particles 100 is 0.1% to 25% of the mass of silicon, the negative electrode active particles 100 can have a higher specific capacity and a higher cycle capacity retention rate.

[0058] In the embodiments of the present application, when a numerical value range from a to b is involved, unless otherwise specified, it means that the numerical value can be any numerical value between a and b, including the endpoint numerical value a and the endpoint numerical value b.

[0059] Furthermore, in the negative electrode active particles 100, the mass of phosphorus is 0.5% to 10% of the mass of silicon. When the mass of phosphorus is 0.5% to 10% of the mass of silicon in the negative electrode active particles 100, the negative electrode active particles 100 can have a higher specific capacity while effectively preventing the size of the silicon phase from being too large, and better preventing Li from being inserted into the lithium battery during the lithium insertion process. 15 The formation of the Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particle 100.

[0060] Furthermore, in the negative electrode active particles 100, the mass of phosphorus is 0.5% to 5% of the mass of silicon. When the mass of phosphorus is 0.5% to 5% of the mass of silicon in the negative electrode active particles 100, the negative electrode active particles 100 can have a higher specific capacity while effectively preventing the size of the silicon phase from being too large, and better preventing Li from being inserted into the lithium battery. 15 The formation of the Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particle 100.

[0061] In some embodiments, the particle size D1 of the silicon-phosphorus particles 30 is in the range of 0.2nm≤D1≤2nm. It is understandable that the diameter D1 of the silicon-phosphorus particles 30 is in the range of 0.2nm to 2nm. Specifically, the particle size D1 of the silicon-phosphorus particles 30 may be, but is not limited to, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1.0nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2.0nm, etc. If the particle size of the silicon-phosphorus particles 30 is too small, the silicon phase cannot be formed, which reduces the embedding of lithium ions and further reduces the specific capacity of the negative electrode active particles 100; if the particle size of the silicon-phosphorus particles 30 is too large, it is easy to generate Li during the lithium embedding process of the negative electrode active particles 100. 15 The Si4 crystal phase, the occurrence of phase change will lead to higher internal stress of the negative electrode active particles 100 and produce a larger volume change, thereby making the negative electrode active particles 100 easier to break and reducing the cycle capacity retention rate of the negative electrode active particles 100.

[0062] Furthermore, the particle size D1 of the silicon-phosphorus particles 30 is in the range of 0.5 nm ≤ D1 ≤ 1.8 nm. When the particle size of the silicon-phosphorus particles 30 is in this range, it is less likely to generate Li during the lithium insertion process of the negative electrode active particles 100. 15 Si4 crystal phase, thereby better improving the structural stability of the negative electrode active particles 100, so that the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0063] Furthermore, the particle size D1 of the silicon-phosphorus particles 30 is in the range of 0.7 nm ≤ D1 ≤ 1.3 nm. When the particle size of the silicon-phosphorus particles 30 is in this range, it is less likely to generate Li during the lithium insertion process of the negative electrode active particles 100. 15 Si4 crystal phase, thereby better improving the structural stability of the negative electrode active particles 100, so that the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0064] In some embodiments, the particle size D2 of the phosphor particles 50 is in the range of 0.1 nm ≤ D2 ≤ 1.5 nm. It can be understood that the diameter D2 of the phosphor particles 50 is in the range of 0.1 nm to 1.5 nm. Specifically, the particle size D2 of the phosphor particles 50 can be, but is not limited to, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, etc. If the particle size of the phosphorus particles 50 is too large, it will cause a waste of space in the pores 11 of the carbon skeleton 10, reduce the space for silicon deposition (i.e., reduce the space for silicon-phosphorus particles 30), and reduce the specific capacity of the negative electrode active particles 100; if the particle size of the phosphorus particles 50 is too small, it will not play a role in isolating the silicon particles, making it difficult to inhibit the growth of the silicon phase in the negative electrode active particles 100, which is not conducive to improving the cycle capacity retention rate of the negative electrode active particles 100.

[0065] Furthermore, the particle size D2 of the phosphorus particles 50 is in the range of 0.3 nm ≤ D2 ≤ 1.3 nm. In this way, the negative electrode active particles 100 can have a higher specific capacity and a higher cycle capacity retention rate.

[0066] Furthermore, the particle size D2 of the phosphorus particles 50 is in the range of 0.3 nm ≤ D2 ≤ 1.0 nm. In this way, the negative electrode active particles 100 can have a higher specific capacity and a higher cycle capacity retention rate.

[0067] See also Figure 3 In some embodiments, the negative electrode active particle 100 further includes a carbon coating layer 70 , and the carbon coating layer 70 is wrapped around the outer periphery of the carbon skeleton 10 .

[0068] It can be understood that the carbon skeleton 10 , the silicon-phosphorus particles 30 and the phosphorus particles 50 are all encapsulated in the carbon coating layer 70 .

[0069] When silicon is exposed on the surface, silicon is in direct contact with the electrolyte, side reactions will occur, active silicon will be consumed, the specific capacity of the negative electrode active material will be reduced, and the cycle capacity retention rate of the negative electrode active particles 100 will continue to decrease with the increase in the number of cycles. In this embodiment, the negative electrode active particles 100 have a carbon coating layer 70, which can prevent silicon from directly contacting the electrolyte when used in a battery, thereby avoiding more side reactions, so that the negative electrode active particles 100 have a higher cycle capacity retention rate, especially high temperature cycle performance.

[0070] In some embodiments, in the negative electrode active particles 100 , the mass ratio of the silicon element to the carbon element is 1:9 to 9:1.

[0071] It can be understood that when the negative electrode active particle 100 includes the carbon coating layer 70, the carbon element is the sum of the carbon elements of the carbon skeleton 10 and the carbon coating layer 70. In other words, in the negative electrode active particle 100, the ratio of the mass of the silicon element to the total mass of the carbon element in the carbon skeleton 10 and the carbon coating layer 70 is 1:9 to 9:1.

[0072] Specifically, in the negative electrode active particles 100, the mass ratio of the silicon element to the carbon element may be, but is not limited to, 1:9, 1:6, 1:4, 1:2, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, etc. If the mass ratio of the silicon element to the carbon element in the negative electrode active particles 100 is too high, when the negative electrode active particles 100 are used in a battery, during the process of lithium insertion in the negative electrode active particles 100, the negative electrode active particles 100 expand too much, repeatedly decompose to generate a new SEI film, accelerate the consumption of the electrolyte in the battery, and further lead to a decrease in the cycle capacity retention rate of the battery; if the mass ratio of the silicon element to the carbon element in the negative electrode active particles 100 is too small, the specific capacity of the negative electrode active particles 100 is reduced, and the energy storage density of the battery is reduced.

[0073] In this embodiment, when the mass ratio of the silicon element to the carbon element in the negative electrode active particles 100 is 1:9 to 9:1, the negative electrode active particles 100 can have a higher specific capacity and a lower expansion rate, which can better prevent the volume expansion of the negative electrode active particles 100 during the lithium insertion process, thereby causing the cycle capacity retention rate of the battery using the negative electrode active particles 100 to drop too quickly.

[0074] Furthermore, in the negative electrode active particles 100, the mass ratio of the silicon element to the carbon element is 0.3 to 5. In this way, the negative electrode active particles 100 can have a higher specific capacity and a lower expansion rate, and can better prevent the volume expansion of the negative electrode active particles 100 during the lithium insertion process, so that the cycle capacity retention rate of the battery using the negative electrode active particles 100 decreases too quickly.

[0075] Furthermore, in the negative electrode active particles 100, the mass ratio of the silicon element to the carbon element is 3:7 to 7:3. In this way, the negative electrode active particles 100 can have a higher specific capacity and a lower expansion rate, which can better prevent the volume expansion of the negative electrode active particles 100 during the lithium insertion process, thereby causing the cycle capacity retention rate of the battery using the negative electrode active particles 100 to drop too quickly.

[0076] In some embodiments, the specific surface area S of the negative electrode active particles 100 is in the range of: 0.15 m 2 / g≤S≤30m 2 Specifically, the specific surface area S of the negative electrode active particles 100 may be, but is not limited to, 0.15 m 2 / g, 0.3m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 3m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 24m 2 / g, 26m 2 / g, 28m 2 / g, 30m 2 / g, etc. When the specific surface area of ​​the negative electrode active particles 100 is small, the contact area between the negative electrode active particles 100 and the electrolyte can be better reduced, so as to avoid excessive consumption of electrolyte during the cycle and reduce the cycle capacity retention rate of the negative electrode particles; however, when the specific surface area of ​​the negative electrode active particles 100 is too small, the size of the negative electrode active particles 100 is large, and the larger size increases the transmission path of lithium ions inside the negative electrode active particles 100, increases the impedance of lithium ion transmission, and makes the kinetic performance of the negative electrode active particles 100 worse; when the specific surface area of ​​the negative electrode active particles 100 is too large, when applied to the battery, the contact area between the negative electrode active particles 100 and the electrolyte increases, and the SEI film increases. During the charge and discharge cycle of the battery, the repeated destruction and growth of the SEI film will consume more electrolyte, which easily reduces the cycle capacity retention rate of the battery.

[0077] Furthermore, the specific surface area S of the negative electrode active particles 100 is in the range of: 1 m 2 / g≤S≤20m 2 This can make the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0078] Furthermore, the specific surface area S of the negative electrode active particles 100 is in the range of: 1 m 2 / g≤S≤10m 2 This can make the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0079] In some embodiments, the median particle size D50 of the negative electrode active particles 100 is in the range of 1 μm ≤ D50 ≤ 20 μm. Specifically, the median particle size D50 of the negative electrode active particles 100 may be, but is not limited to, 1 μm, 2 μm, 5 μm, 7 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, etc.

[0080] In this embodiment, if the median particle size D50 of the negative electrode active particles 100 is too large, when the negative electrode active particles 100 are used in lithium batteries, the transmission path of lithium ions inside the negative electrode active particles 100 increases, the transmission impedance of lithium ions increases, and the kinetics deteriorates; if the median particle size D50 of the negative electrode active particles 100 is too small, the specific surface area of ​​the negative electrode active particles 100 increases, the contact area between the negative electrode active particles 100 and the electrolyte increases, and the SEI film increases. During the charge and discharge cycle of the battery, the repeated destruction and growth of the SEI film will consume more electrolyte, which easily reduces the cycle capacity retention rate of the battery. When the range of the median particle size D50 of the negative electrode active particles 100 is: 1μm≤D50≤20μm, the negative electrode active particles 100 can have good kinetic performance and a high cycle capacity retention rate.

[0081] Furthermore, the median particle size D50 of the negative electrode active particles 100 is in the range of 3 μm ≤ D50 ≤ 15 μm. In this way, the negative electrode active particles 100 can have good dynamic performance and high cycle capacity retention rate.

[0082] Furthermore, the median particle size D50 of the negative electrode active particles 100 is in the range of 5 μm ≤ D50 ≤ 12 μm. In this way, the negative electrode active particles 100 can have good dynamic performance and high cycle capacity retention rate.

[0083] In some embodiments, the thickness L of the carbon coating layer 70 is in the range of 1 nm ≤ L ≤ 2000 nm. Specifically, the thickness L of the carbon coating layer 70 may be, but is not limited to, 1 nm, 3 nm, 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 150 nm, 200 nm, 300 nm, 400 nm, 500 nm, 800 nm, 1000 nm, 1250 nm, 1500 nm, 1750 nm, 2000 nm, etc.

[0084] In this embodiment, if the thickness L of the carbon coating layer 70 is too thick, the carbon content in the negative electrode active particles 100 is too high, the proportion of silicon decreases, and the specific capacity of the negative electrode active particles 100 is reduced; if the thickness L of the carbon coating layer 70 is too thin, the carbon coating layer 70 does not completely coat the carbon skeleton 10, which easily leads to incomplete isolation of the silicon phosphorus particles 30 from the electrolyte, increased side reactions, and reduced cycle capacity retention rate of the negative electrode active particles 100.

[0085] Furthermore, the range of the thickness L of the carbon coating layer 70 is: 2nm≤L≤1000nm. In this way, the negative electrode active particles 100 can have a higher specific capacity and a higher cycle capacity retention rate.

[0086] Furthermore, the thickness L of the carbon coating layer 70 is in the range of 2 nm ≤ L ≤ 500 nm. This allows the negative electrode active particles 100 to have a higher specific capacity and a higher cycle capacity retention rate.

[0087] Furthermore, the thickness L of the carbon coating layer 70 is in the range of 5 nm ≤ L ≤ 100 nm. This allows the negative electrode active particles 100 to have a higher specific capacity and a higher cycle capacity retention rate.

[0088] In some embodiments, the negative electrode active particles 100 include, by mass, 10% to 89.99% carbon, 10% to 89.99% silicon, and 0.01% to 15% phosphorus.

[0089] Specifically, the mass fraction of carbon in the negative electrode active particles 100 may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 89.99%, etc. In the negative electrode active particles 100, if the carbon content is too much, the specific capacity of the negative electrode active particles 100 is reduced; if the carbon content is too little, the buffering effect on the expansion of silicon when lithium is inserted is reduced, resulting in an increase in the expansion of the negative electrode active particles 100 when lithium is inserted, thereby reducing the cycle performance of the negative electrode active particles 100.

[0090] Specifically, the mass fraction of silicon in the negative electrode active particles 100 may be, but is not limited to, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 89.99%, etc. In the negative electrode active particles 100, if the content of silicon is too high, the expansion of the negative electrode active particles 100 during lithium insertion increases, and the cycle performance deteriorates; if the content of silicon is too low, the specific capacity of the negative electrode active particles 100 is reduced.

[0091] Specifically, the mass fraction of phosphorus in the negative electrode active particles 100 may be, but is not limited to, 0.01%, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc. In the negative electrode active particles 100, if the phosphorus content is too much, the ratio of silicon to carbon will decrease, and the specific capacity and cycle performance of the negative electrode active particles 100 will be reduced; if the phosphorus content is too little, it will not be able to prevent the size of silicon from growing, and the conductivity of the negative electrode active particles 100 will be reduced, so that the cycle performance of the negative electrode active particles 100 will deteriorate.

[0092] Furthermore, the negative electrode active particles 100 include 30% to 69.7% carbon, 30% to 69.7% silicon and 0.3% to 10% phosphorus by mass, so that the negative electrode active particles 100 have better specific capacity, higher conductivity and cycle capacity retention rate.

[0093] Furthermore, the negative electrode active particles 100 include 40% to 58.2% carbon, 40% to 58.2% silicon and 0.8% to 5% phosphorus by mass, so that the negative electrode active particles 100 have better specific capacity, higher conductivity and cycle capacity retention rate.

[0094] In some embodiments, the conductivity of the negative electrode active particles 100 is greater than or equal to 5.7 S / cm. Further, the conductivity of the negative electrode active particles 100 may be, but is not limited to, greater than or equal to 6.3 S / cm, or greater than or equal to 6.6 S / cm, or greater than or equal to 7 S / cm, or greater than or equal to 7.5 S / cm, or greater than or equal to 8 S / cm.

[0095] In some embodiments, the conductivity of the negative electrode active particles 100 is 5.7 S / cm to 8.7 S / cm. Specifically, the conductivity of the negative electrode active particles 100 may be, but is not limited to, 5.7 S / cm, 6 S / cm, 6.2 S / cm, 6.5 S / cm, 6.8 S / cm, 7 S / cm, 7.3 S / cm, 7.5 S / cm, 7.8 S / cm, 8 S / cm, 8.25 S / cm, 8.5 S / cm, 8.7 S / cm, etc.

[0096] In some embodiments, the specific capacity of the negative electrode active particles 100 ranges from 1291 mAh / g to 1700 mAh / g. Specifically, the specific capacity of the negative electrode active particles 100 may be, but is not limited to, 1291 mAh / g, 1300 mAh / g, 1350 mAh / g, 1400 mAh / g, 1450 mAh / g, 1500 mAh / g, 1550 mAh / g, 1600 mAh / g, 1650 mAh / g, 1700 mAh / g, etc.

[0097] In some embodiments, the 100 cycle capacity retention rate of the negative electrode active particles 100 is greater than or equal to 88%. Further, the 100 cycle capacity retention rate of the negative electrode active particles 100 is greater than or equal to 92%. Still further, the 100 cycle capacity retention rate of the negative electrode active particles 100 is greater than or equal to 94%. Specifically, the 100 cycle capacity retention rate of the negative electrode active particles 100 can be, but is not limited to, 88%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, etc.

[0098] The negative electrode active particles 100 of the embodiments of the present application can be prepared by the methods described in the following embodiments of the present application. In addition, they can also be prepared by other methods. The preparation methods of the embodiments of the present application are merely one or more preparation methods of the negative electrode active particles 100 of the present application and should not be construed as limiting the negative electrode active particles 100 provided in the embodiments of the present application.

[0099] See also Figure 4 The present application also provides a method for preparing negative electrode active particles 100, which includes:

[0100] S201, providing a carbon skeleton 10 (which may also be called porous carbon or porous carbon precursor), wherein the carbon skeleton 10 has a plurality of pores 11; and

[0101] S202, alternately introducing silicon source gas and phosphorus source gas into the carbon skeleton 10 to deposit silicon-phosphorus particles 30 and phosphorus particles 50 in the plurality of pores 11 to obtain negative electrode active particles 100, wherein the negative electrode active particles 100 include the carbon skeleton 10, silicon-phosphorus particles 30 and phosphorus particles 50.

[0102] The preparation method of the negative electrode active particles 100 of the embodiment of the present application is to alternately introduce silicon source gas and phosphorus source gas into the porous carbon skeleton 10 to perform vapor deposition, thereby depositing silicon phosphorus particles 30 and phosphorus particles 50 in multiple pores 11 of the carbon skeleton 10. The silicon source gas and the phosphorus source gas are alternately introduced. After a period of silicon deposition, phosphorus deposition is performed. This can inhibit the growth of the silicon phase, block the continuous growth of the silicon nucleus, and avoid the connection between adjacent silicon particles, thereby controlling the continuous silicon size. In addition, a part of the phosphorus will penetrate into the silicon particles to form silicon phosphorus particles 30, and the other part of the phosphorus will be directly deposited to form phosphorus particles 50. The phosphorus particles 50 can further isolate the silicon particles, thereby better avoiding the connection between the silicon phosphorus particles 30 deposited last time and the silicon formed next time, forming large-sized silicon phosphorus particles 30; the smaller silicon phosphorus particles 30 make the negative electrode active particles 100 effectively prevent Li from being inserted into lithium. 15 The formation of Si4 crystal phase can reduce the volume change of negative electrode active particles 100 during lithium insertion and better weaken the Li 15 The formation of Si4 crystal phase causes the negative electrode active particles 100 to break, so that the negative electrode active particles 100 have a more stable silicon structure, thereby having a higher cycle capacity retention rate. In addition, phosphorus enters the silicon phase to form silicon phosphorus particles 30. The distribution of phosphorus in the silicon phase can provide more free electrons, increase the carrier concentration in the silicon phase, and thus improve the conductivity of the negative electrode active particles 100; the improvement of the conductivity of the negative electrode active particles 100 will reduce the polarization of lithium insertion and extraction, and can help lithium to be more fully extracted from the inside of the negative electrode active particles 100, which helps to reduce the lithium loss caused by the insufficient kinetic performance of silicon, thereby improving the specific capacity and cycle retention rate of the negative electrode active particles 100.

[0103] In some embodiments, the specific surface area S' of the carbon skeleton 10 is in the range of 500 m 2 / g≤S'≤4000m 2 / g. Specifically, the specific surface area of ​​the carbon skeleton 10 may be, but is not limited to, 500m 2 / g, 600m 2 / g、800m 2 / g、1000m 2 / g、1200m2 / g、1400m 2 / g、1600m 2 / g, 2000m 2 / g, 2500m 2 / g、3000m 2 / g、3500m 2 / g, 4000m 2 / g, etc. If the specific surface area of ​​the carbon skeleton 10 is too high, it means that there are a large number of pores 11 in the carbon skeleton 10, which makes the silicon content that can be deposited too high, and the silicon-phosphorus particles 30 in the same pore 11 are easily connected to form a continuous silicon phase of larger particles, resulting in excessive expansion of a single silicon-phosphorus particle 30 during lithium insertion; if the specific surface area of ​​the carbon skeleton 10 is too low, the content of deposited silicon is insufficient, which easily makes the specific capacity of the obtained negative electrode active particles 100 too low.

[0104] Furthermore, the specific surface area S' of the carbon skeleton 10 is in the range of 600 m 2 / g≤S'≤3000m 2 In this way, the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 can be better controlled, so that the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 is smaller, thereby having a better cycle capacity retention rate, and the negative electrode active particles 100 can have a higher specific capacity.

[0105] Furthermore, the specific surface area S' of the carbon skeleton 10 is in the range of 800 m 2 / g≤S'≤2000m 2 In this way, the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 can be better controlled, so that the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 is smaller, thereby having a better cycle capacity retention rate, and the negative electrode active particles 100 can have a higher specific capacity.

[0106] In some embodiments, in S202, the step of alternately introducing the silicon source gas and the phosphorus source gas into the carbon skeleton 10 includes the following steps that are performed alternately multiple times:

[0107] S2021, introducing silicon source gas, and performing first vapor deposition at a first temperature T1 of 450° C. ≤ T1 ≤ 700° C.; and

[0108] Optionally, the introduction of the silicon source gas and the first vapor deposition at the first temperature T1 of 450°C≤T1≤700°C include: a first mixed gas obtained by mixing the silicon source gas with a first carrier gas, the first mixed gas being introduced into the carbon skeleton 10, and the first vapor deposition at the first temperature T1 of 450°C≤T1≤700°C, wherein the volume fraction of the silicon source gas in the first mixed gas is 1% to 70%. After the introduction of the first mixed gas, the silicon source gas enters the pores 11 of the carbon skeleton 10, and decomposes and deposits in the pores 11 to form silicon particles.

[0109] Optionally, the silicon source gas is a silicon-containing gas, and the silicon-containing gas may be but is not limited to at least one of monosilane, disilane, dichlorosilane, trichlorosilane, and the like.

[0110] Optionally, the first carrier gas may be, but is not limited to, at least one of nitrogen, argon, hydrogen, and the like.

[0111] Specifically, the first temperature T1 can be, but is not limited to, 450°C, 480°C, 500°C, 530°C, 550°C, 580°C, 600°C, 630°C, 650°C, 680°C, 700°C, etc. If the first temperature is too high, the reaction speed of the silicon source gas will be too fast, and the silicon source gas will not have time to enter the pores 11 of the carbon skeleton 10 before it begins to deposit. The deposition of silicon on the surface of the carbon skeleton 10 will cause the negative electrode active particles 100 to embed lithium. When silicon expands, it is not restricted by the space of the carbon skeleton 10, which increases the expansion rate of the entire negative electrode active particles 100 and deteriorates the cycle performance. In addition, when silicon is deposited on the surface, the size of silicon will not be restricted by the size of the pores 11 in the carbon skeleton 10 and will continue to grow. The excessively large silicon size will cause the generation of Li+ when embedding lithium. 15 Si4 phase, the cycle performance deteriorates; if the first temperature is too low, the silicon source gas is difficult to decompose into silicon and deposit.

[0112] Specifically, the volume fraction of the silicon source gas in the first mixed gas may be, but is not limited to, 1%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, etc. If the volume fraction of the silicon source gas is too high (the concentration is too high), the silicon source gas will be more likely to decompose independently outside the pores 11 of the carbon skeleton 10 to form silicon particles, rather than entering the pores 11 of the carbon skeleton 10 for deposition; if the volume fraction of the silicon source gas is too small, the reaction speed of the silicon source gas is too slow, and the reaction efficiency of silicon deposition is reduced.

[0113] Furthermore, the volume fraction of the silicon source gas in the first mixed gas is 5% to 50%, which can make the silicon deposition efficiency higher and allow more silicon source gas to enter the pores 11 of the carbon skeleton 10 for silicon deposition.

[0114] Furthermore, the volume fraction of the silicon source gas in the first mixed gas is 5% to 40%, which can make the silicon deposition efficiency higher and allow more silicon source gas to enter the pores 11 of the carbon skeleton 10 for silicon deposition.

[0115] Furthermore, the volume fraction of the silicon source gas in the first mixed gas is 5% to 30%, which can make the silicon deposition efficiency higher and allow more silicon source gas to enter the pores 11 of the carbon skeleton 10 for silicon deposition.

[0116] S2022, introducing phosphorus source gas, and performing a second vapor deposition at a second temperature T2 of 300°C ≤ T2 ≤ 900°C.

[0117] Optionally, the introduction of the phosphorus source gas and the second vapor deposition at the second temperature T2 of 300°C≤T2≤900°C include: a second mixed gas of the phosphorus source gas and a second carrier gas, the second mixed gas is introduced into the carbon skeleton 10, and the second vapor deposition is performed at the second temperature T2 of 300°C≤T2≤900°C, wherein the volume fraction of the phosphorus source gas in the second mixed gas is 0.1% to 70%. After the introduction of the second mixed gas, the phosphorus source gas enters the pores 11 of the carbon skeleton 10, and decomposes and deposits in the pores 11 to form phosphorus particles 50, and part of the phosphorus penetrates into the silicon particles to form silicon phosphorus particles 30.

[0118] Optionally, the phosphorus source gas is a phosphorus-containing gas, and the phosphorus-containing gas may be but is not limited to at least one of phosphine, trimethyl phosphine, triethyl phosphine, and the like.

[0119] Optionally, the second carrier gas may be, but is not limited to, at least one of nitrogen, argon, hydrogen, etc. The second carrier gas may be the same as or different from the first carrier gas, which is not specifically limited in the present application.

[0120] Optionally, the second temperature T2 may be, but is not limited to, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc. If the second temperature is too high, the deposited silicon and carbon may react to form SiC, thereby losing activity and reducing the specific capacity of the negative electrode active particles 100; if the second temperature is too low, the phosphorus source gas may not be decomposed, making it difficult to deposit phosphorus.

[0121] Furthermore, the second temperature ranges from 450° C. to 700° C. This can better prevent silicon from reacting with carbon, and can also make the phosphorus source gas have a faster decomposition speed, thereby having a higher deposition efficiency.

[0122] Specifically, in the second mixed gas, the volume fraction of the phosphorus source gas may be, but is not limited to, 0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, etc. If the volume fraction of the phosphorus source gas is too high (i.e., the concentration is too high), the phosphorus source gas is more likely to independently decompose outside the pores 11 of the carbon skeleton 10 to form phosphorus particles 50, rather than entering the pores 11 for deposition, thereby not only reducing the inhibitory effect of the phosphorus particles 50 on the size growth of the silicon phase, but also making the phosphorus particles 50 unable to provide more free electrons for silicon, not only reducing the conductivity of the negative electrode active particles 100, but also reducing the cycle capacity retention rate of the negative electrode active particles 100; if the volume fraction of the phosphorus source gas is too low (i.e., the concentration is too low), the reaction rate of the phosphorus source gas is too slow, and the reaction efficiency of silicon deposition is reduced.

[0123] Furthermore, in the second mixed gas, the volume fraction of the phosphorus source gas is 0.5% to 45%, which can improve the efficiency of forest production and allow more phosphorus source gas to enter the pores 11 of the carbon skeleton 10 for phosphorus deposition.

[0124] Furthermore, in the second mixed gas, the volume fraction of the phosphorus source gas is 0.5% to 30%, which can improve the efficiency of forest production and allow more phosphorus source gas to enter the pores 11 of the carbon skeleton 10 for phosphorus deposition.

[0125] Furthermore, in the second mixed gas, the volume fraction of the phosphorus source gas is 1% to 20%, which can improve the efficiency of forest production and allow more phosphorus source gas to enter the pores 11 of the carbon skeleton 10 for phosphorus deposition.

[0126] Furthermore, in the second mixed gas, the volume fraction of the phosphorus source gas is 1% to 10%, which can improve the efficiency of forest production and allow more phosphorus source gas to enter the pores 11 of the carbon skeleton 10 for phosphorus deposition.

[0127] Optionally, the first temperature and the second temperature may be the same or different. When the first temperature and the second temperature are the same, the temperature adjustment process when silicon deposition and phosphorus deposition are performed alternately can be saved, the reaction progress can be accelerated, and the production efficiency can be improved.

[0128] It is understandable that the first vapor deposition is silicon deposition, and the second vapor deposition is phosphorus deposition. It is understandable that in this embodiment, the first vapor deposition and the second vapor deposition are performed alternately for multiple times. When the first vapor deposition is performed, the silicon source gas decomposes in the multiple pores 11 of the carbon skeleton 10 to perform silicon deposition; when the second vapor deposition is performed, the phosphorus source gas decomposes in the multiple pores 11 of the carbon skeleton 10 to perform phosphorus deposition. When phosphorus deposition is performed, part of the phosphorus enters the silicon particles, thereby forming silicon-phosphorus particles 30, and part of the phosphorus forms independent phosphorus particles 50.

[0129] It should be noted that there is no order of precedence between the first vapor deposition and the second vapor deposition. The first vapor deposition (silicon deposition) can be performed first, and then the second vapor deposition (phosphorus deposition); or the second vapor deposition (phosphorus deposition) can be performed first, and then the first vapor deposition (silicon deposition).

[0130] Optionally, the number of times n that the first vapor deposition and the second vapor deposition are alternately performed is: n≥5. Further, the number of times n that the first vapor deposition and the second vapor deposition are alternately performed is: 5≤n≤60. Specifically, the number of times n that the first vapor deposition and the second vapor deposition are alternately performed can be, but is not limited to, 5, 8, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, etc. The more times the first vapor deposition and the second vapor deposition are alternately performed, the shorter the time for each first vapor deposition and the second vapor deposition is when the total deposition time is constant, so that the size of the formed silicon-phosphorus particles 30 is smaller, and thus the size of the continuous silicon phase is smaller, which is more conducive to improving the cycle capacity retention rate of the negative electrode active particles 100, but too many alternations increase the complexity of the process and the preparation cost.

[0131] Furthermore, the number of times n that the first vapor deposition and the second vapor deposition are alternately performed is: 10≤n≤50. This can better reduce the preparation cost of the negative electrode active particles 100, and can also make the size of the silicon phosphorus particles 30 in the prepared negative electrode active particles 100 smaller, so that the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0132] Furthermore, the number of times n that the first vapor deposition and the second vapor deposition are alternately performed is: 20≤n≤40. This can better reduce the preparation cost of the negative electrode active particles 100, and can also make the size of the silicon phosphorus particles 30 in the prepared negative electrode active particles 100 smaller, so that the negative electrode active particles 100 have a higher cycle capacity retention rate.

[0133] It can be understood that performing the first vapor deposition once and the second vapor deposition once is called alternating once. For example, when the alternating times b=5, the first vapor deposition and the second vapor deposition are respectively performed 5 times and the two are performed alternately in sequence.

[0134] In some embodiments, the total volume of the silicon source gas introduced alternately for multiple times is V1, and the total volume of the phosphorus source gas introduced alternately for multiple times is V2, wherein 3≤V1 / V2≤999. Specifically, V1 / V2 can be, but is not limited to, 3, 5, 10, 30, 50, 80, 100, 130, 150, 180, 200, 300, 400, 500, 600, 700, 800, 900, 999, etc. If V1 / V2 is too small, the phosphorus content is too high, and the proportion of active silicon in the negative electrode active particles 100 decreases, thereby reducing the specific capacity of the negative electrode active particles 100, which is not conducive to improving the energy density of the battery using the negative electrode active particles 100; if the phosphorus content is too low, it is difficult to effectively prevent the growth of silicon size, which easily makes the size of the silicon phase too large, and it is easy to form Li during the lithium insertion process. 15 The Si4 crystal phase reduces the cycle capacity protection rate of the negative electrode active particles 100.

[0135] Furthermore, the ratio of the total volume V1 of the silicon source gas alternately introduced multiple times to the total volume V2 of the phosphorus source gas alternately introduced multiple times is in the range of 19 to 199. This can make the negative electrode active particles 100 have a higher specific capacity while effectively preventing the silicon phase from being too large, and better preventing the Li 15 The formation of the Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particle 100.

[0136] Furthermore, the ratio of the total volume V1 of the silicon source gas alternately introduced multiple times to the total volume V2 of the phosphorus source gas alternately introduced multiple times is in the range of 19 to 100. This can make the negative electrode active particles 100 have a higher specific capacity while effectively preventing the silicon phase from being too large, and better preventing Li 15 The formation of the Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particle 100.

[0137] In some embodiments, the time for each first vapor deposition is t1, and the time for each second vapor deposition is t2, wherein 1≤t1 / t2≤1200. Specifically, the ratio of the time t1 for a single first vapor deposition to the time t2 for a single second vapor deposition may be, but is not limited to, 1, 3, 5, 8, 10, 13, 15, 18, 20, 30, 50, 80, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, etc. If t1 / t2 is too large, it is easy for the silicon particles to grow too large during the first vapor deposition, thereby making the size of the silicon-phosphorus particles 30 eventually too large, and the size of the silicon phase in the negative electrode active particles 100 too large, which makes it easier for the negative electrode active particles 100 to generate Li when lithium is inserted.15 Si4 crystal phase, during the formation of the crystal phase, the negative electrode active particles 100 will cause higher internal stress and produce greater volume changes, which will deteriorate the cycle performance of the negative electrode active particles 100; in addition, the phosphorus deposition time is too short, so that the phosphorus in the negative electrode active particles 100 is too little, and it is difficult to effectively increase the concentration of carriers in the silicon phase, which is not conducive to improving the conductivity of the negative electrode active particles 100; t1 / t2 is too small, then the silicon content in the formed negative electrode active particles 100 is too little, which reduces the specific capacity of the negative electrode active particles 100.

[0138] Furthermore, the ratio of the time t1 for a single first vapor deposition to the time t2 for a single second vapor deposition is in the range of 1≤t1 / t2≤800. In this way, the negative electrode active particles 100 can have a higher specific capacity while better controlling the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0139] Furthermore, the ratio of the time t1 of a single first vapor deposition to the time t2 of a single second vapor deposition is in the range of 1≤t1 / t2≤600. In this way, the negative electrode active particles 100 can have a higher specific capacity, and the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100 can be better controlled, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0140] Furthermore, the ratio of the time t1 of a single first vapor deposition to the time t2 of a single second vapor deposition is in the range of 1≤t1 / t2≤300. In this way, the negative electrode active particles 100 can have a higher specific capacity, and the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100 can be better controlled, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0141] Furthermore, the ratio of the time t1 of a single first vapor deposition to the time t2 of a single second vapor deposition is in the range of 2≤t1 / t2≤100. In this way, the negative electrode active particles 100 can have a higher specific capacity, and the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100 can be better controlled, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0142] Furthermore, the ratio of the time t1 for a single first vapor deposition to the time t2 for a single second vapor deposition is in the range of 5≤t1 / t2≤50. In this way, the negative electrode active particles 100 can have a higher specific capacity, and the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100 can be better controlled, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0143] Furthermore, the ratio of the time t1 for a single first vapor deposition to the time t2 for a single second vapor deposition is in the range of 5≤t1 / t2≤20. In this way, the negative electrode active particles 100 can have a higher specific capacity, and the size of the silicon-phosphorus particles 30 in the final negative electrode active particles 100 can be better controlled, so that the negative electrode active particles 100 have a smaller silicon phase size, thereby having better cycle performance.

[0144] Optionally, the time t1 for a single first vapor deposition is in the range of 1min≤t1≤10h. Specifically, the time t1 for a single first vapor deposition may be, but is not limited to, 1min, 5min, 10min, 20min, 30min, 40min, 50min, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. If the time t1 for a single first vapor deposition is too long, it is easy for the silicon particles to grow too large, the formed silicon-phosphorus particles 30 to be too large, and the size of the silicon phase in the negative electrode active particles 100 to be too large, so that the negative electrode active particles 100 are easier to generate Li when inserting lithium. 15 Si4 crystal phase, during the formation of the crystal phase, the negative electrode active particles 100 will cause higher internal stress and produce greater volume changes, which will deteriorate the cycle performance of the negative electrode active particles 100; if the time t1 of a single first vapor deposition is too short, the first vapor deposition and the second vapor deposition will alternate too many times, which will increase the production process, reduce production efficiency, and increase production costs; in addition, when the time of the second vapor deposition is too long, this will reduce the silicon content in the negative electrode active particles 100 and reduce the specific capacity of the negative electrode active particles 100.

[0145] Furthermore, the time t1 for a single first vapor deposition is in the range of 5min≤t1≤5h. When the time for a single first vapor deposition is in this range, the size of the silicon particles can be controlled within a more suitable range, so that the negative electrode active particles 100 have better cycle performance, and at the same time, the number of alternations between the first vapor deposition and the second vapor deposition can be reduced, thereby improving production efficiency and reducing production costs.

[0146] Furthermore, the time t1 for a single first vapor deposition is in the range of 5min≤t1≤2h. When the time for a single first vapor deposition is in this range, the size of the silicon particles can be controlled within a more suitable range, so that the negative electrode active particles 100 have better cycle performance, and at the same time, the number of alternations between the first vapor deposition and the second vapor deposition can be reduced, thereby improving production efficiency and reducing production costs.

[0147] Furthermore, the time t1 for a single first vapor deposition is in the range of 10min≤t1≤1h. When the time for a single first vapor deposition is in this range, the size of the silicon particles can be controlled within a more suitable range, so that the negative electrode active particles 100 have better cycle performance, and at the same time, the number of alternations between the first vapor deposition and the second vapor deposition can be reduced, thereby improving production efficiency and reducing production costs.

[0148] Optionally, the time t2 for a single second vapor deposition is in the range of 30s≤t2≤5h. Specifically, the time t2 for a single second vapor deposition may be, but is not limited to, 30s, 1min, 5min, 10min, 20min, 30min, 30min, 45min, 1h, 2h, 3h, 4h, 5h. If the time t2 for a single second vapor deposition is too long, too much phosphorus will be deposited, the silicon ratio will be reduced, and the specific capacity of the negative electrode active particles 100 will be reduced; if the time t2 for a single second vapor deposition is too short, the growth of the silicon phase size cannot be prevented, and the cycle performance of the negative electrode active particles 100 will be reduced.

[0149] Furthermore, the range of the time t2 for a single second vapor deposition is 1min≤t2≤2h. When the time t2 for a single second vapor deposition is within this range, the negative electrode active particles 100 can have a higher specific capacity and a more appropriate phosphorus content, thereby better inhibiting the growth of the silicon phase size and improving the cycle performance of the negative electrode active particles 100.

[0150] Furthermore, the range of the time t2 for a single second vapor deposition is 1min≤t2≤1h. When the time t2 for a single second vapor deposition is within this range, the negative electrode active particles 100 can have a higher specific capacity and a more appropriate phosphorus content, thereby better inhibiting the growth of the silicon phase size and improving the cycle performance of the negative electrode active particles 100.

[0151] Furthermore, the time t2 for a single second vapor deposition is in the range of 2min≤t2≤40min. When the time t2 for a single second vapor deposition is in this range, the negative electrode active particles 100 can have a higher specific capacity and a more appropriate phosphorus content, thereby better inhibiting the growth of the silicon phase size and improving the cycle performance of the negative electrode active particles 100.

[0152] Optionally, the ratio of the gas flow rate of the silicon source gas for the first vapor deposition to the gas flow rate of the phosphorus source gas for the second vapor deposition is 0.01 to 1000. Specifically, the ratio of the gas flow rate of the silicon source for the first vapor deposition to the gas flow rate of the phosphorus source for the second vapor deposition can be, but is not limited to, 0.01, 0.04, 0.08, 0.1, 0.5, 1, 3, 5, 10, 12, 14, 15, 16, 18, 20, 30, 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, etc. If the ratio of the gas flow rate of the silicon source gas for the first vapor phase precipitation to the gas flow rate of the phosphorus source gas for the second vapor phase deposition is too large, then when the first vapor phase deposition is performed, it means that the gas flow rate of the silicon source gas is too large, making it easier for silicon particles to be deposited on the outside of the carbon skeleton 10, thereby increasing the expansion of the negative electrode active particles 100 when lithium is inserted, and reducing the cycle performance of the negative electrode active particles 100; if the ratio of the gas flow rate of the silicon source gas for the first vapor phase precipitation to the gas flow rate of the phosphorus source gas for the second vapor phase deposition is too small, it means that the gas flow rate of the phosphorus source gas is too large, making it easier for the phosphorus particles 50 to be deposited on the outside of the carbon skeleton 10, reducing the amount of phosphorus particles 50 in the pores 11 of the carbon skeleton 10, and reducing the inhibitory effect of the phosphorus particles 50 on the growth of the silicon phase size, so that the size of the silicon phosphorus particles 30 in the obtained negative electrode active particles 100 increases, and the cycle performance deteriorates.

[0153] Furthermore, the ratio of the gas flow rate of the silicon source gas for the first vapor deposition to the gas flow rate of the phosphorus source gas for the second vapor deposition is 0.1 to 500. In this way, both silicon and phosphorus can be better deposited in the pores 11 of the carbon skeleton 10, and the amount of phosphorus and silicon deposited outside the carbon skeleton 10 can be avoided. In addition, the growth of the silicon phase size can be better suppressed, and the cycle performance of the negative electrode active particles 100 can be improved. Furthermore, the negative electrode active particles 100 can also have a higher silicon content, thereby having a higher specific capacity.

[0154] Furthermore, the ratio of the gas flow rate of the silicon source gas for the first vapor deposition to the gas flow rate of the phosphorus source gas for the second vapor deposition is 0.1 to 100. In this way, both silicon and phosphorus can be better deposited in the pores 11 of the carbon skeleton 10, and the amount of phosphorus and silicon deposited outside the carbon skeleton 10 can be avoided. In addition, the growth of the silicon phase size can be better suppressed, and the cycle performance of the negative electrode active particles 100 can be improved. Furthermore, the negative electrode active particles 100 can also have a higher silicon content, thereby having a higher specific capacity.

[0155] Furthermore, the ratio of the gas flow rate of the silicon source gas for the first vapor deposition to the gas flow rate of the phosphorus source gas for the second vapor deposition is 0.1 to 20. In this way, both silicon and phosphorus can be better deposited in the pores 11 of the carbon skeleton 10, and the amount of phosphorus and silicon deposited outside the carbon skeleton 10 can be avoided. In addition, the growth of the silicon phase size can be better suppressed, and the cycle performance of the negative electrode active particles 100 can be improved. Furthermore, the negative electrode active particles 100 can also have a higher silicon content, thereby having a higher specific capacity.

[0156] Furthermore, the ratio of the gas flow rate of the silicon source gas for the first vapor deposition to the gas flow rate of the phosphorus source gas for the second vapor deposition is 1 to 10. In this way, both silicon and phosphorus can be better deposited in the pores 11 of the carbon skeleton 10, and the amount of phosphorus and silicon deposited outside the carbon skeleton 10 can be avoided. In addition, the growth of the silicon phase size can be better suppressed, and the cycle performance of the negative electrode active particles 100 can be improved. Furthermore, the negative electrode active particles 100 can also have a higher silicon content, thereby having a higher specific capacity.

[0157] See also Figure 5 The present application also provides a method for preparing negative electrode active particles 100, which includes:

[0158] S301, providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11; and

[0159] S302, alternately introducing silicon source gas and phosphorus source gas into the carbon skeleton 10 to deposit silicon phosphorus particles 30 and phosphorus particles 50 in the plurality of pores 11; and

[0160] S303 , forming a carbon coating layer 70 on the surface of the carbon skeleton 10 having the silicon phosphorus particles 30 and the phosphorus particles 50 .

[0161] Optionally, an alkane gas (such as acetylene gas) is introduced to form a carbon coating layer 70 on the surface of the carbon skeleton 10 having the silicon phosphorus particles 30 and the phosphorus particles 50 by chemical vapor deposition (CVD). In a specific embodiment, acetylene gas is introduced at a temperature of 650° C. to 850° C. (such as 650° C., 700° C., 750° C., 800° C., 850° C., etc.) for 1 h to 3 h (such as 1 h, 1.5 h, 2 h, 2.5 h, 3 h, etc.) to obtain the carbon coating layer 70.

[0162] In another embodiment, an organic carbon source such as citric acid, asphalt, etc. is used to coat the carbon skeleton 10 , and then carbonized to form a carbon coating layer 70 coated on the outer surface of the carbon skeleton 10 .

[0163] The negative electrode active particles 100 of the present application are further described below through specific examples.

[0164] Example 1

[0165] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0166] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0167] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0168] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 30 minutes;

[0169] 4) a second mixed gas obtained by mixing phosphine gas and hydrogen gas is introduced into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 1%, the gas flow rate of the second mixed gas is 0.1 L / min, and the second mixed gas is stopped after the vapor deposition reaction for 15 minutes; step 3) and step 4) are alternately deposited 40 times in sequence; and

[0170] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0171] The negative electrode active particles 100 obtained in Example 1 were subjected to a scanning electron microscope (SEM) test, and the obtained SEM image is as follows: Figure 6The negative electrode active particles 100 obtained in Example 1 were tested by an X-ray energy dispersive spectrometer (EDS), and the EDS graph of silicon element was obtained as shown in FIG. Figure 7 As shown, the EDS diagram of phosphorus is as follows Figure 8 As shown. Figures 6 to 8 It can be seen that the silicon phosphorus particles 30 and the phosphorus particles 50 are dispersed in the carbon skeleton 10 (pores 11 ) of the negative electrode active particles 100 prepared in the embodiment of the present application.

[0172] According to tests, the mass fraction of carbon in the negative electrode active particles 100 obtained in Example 1 is 47.97 wt %, the mass fraction of silicon is 50.79 wt %, and the mass fraction of phosphorus is 1.24 wt %.

[0173] Example 2

[0174] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0175] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0176] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0177] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 1 hour;

[0178] 4) introducing a second mixed gas obtained by mixing phosphine gas and hydrogen into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 1%, and the gas flow rate of the second mixed gas is 0.1 L / min, and stopping the introduction of the second mixed gas after the vapor deposition reaction for 5 minutes; performing step 3) and step 4) alternately for 20 times; and

[0179] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0180] Example 3

[0181] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0182] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m2 / g.

[0183] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0184] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 30 minutes;

[0185] 4) a second mixed gas obtained by mixing phosphine gas and hydrogen gas is introduced into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 5%, the gas flow rate of the second mixed gas is 0.1 L / min, and the second mixed gas is stopped after the vapor deposition reaction for 10 minutes; step 3) and step 4) are alternately deposited 40 times in sequence; and

[0186] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0187] Example 4

[0188] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0189] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0190] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0191] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 30 minutes;

[0192] 4) cooling to 500° C., introducing a second mixed gas obtained by mixing phosphine gas and hydrogen into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 5%, and the gas flow rate of the second mixed gas is 0.1 L / min, and stopping the introduction of the second mixed gas after the vapor deposition reaction for 2.5 minutes; performing step 3) and step 4) alternately for 40 times; and

[0193] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0194] Example 5

[0195] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0196] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0197] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0198] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.5 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 6 minutes;

[0199] 4) cooling to 500° C., introducing a second mixed gas obtained by mixing phosphine gas and hydrogen into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 5%, and the gas flow rate of the second mixed gas is 0.2 L / min, and stopping the introduction of the second mixed gas after the vapor deposition reaction for 1 minute; performing step 3) and step 4) alternately for 40 times; and

[0200] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0201] Example 6

[0202] The negative electrode active particles 100 of this embodiment are prepared by the following steps:

[0203] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 842 m 2 / g.

[0204] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 510° C.;

[0205] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 2 hours;

[0206] 4) a second mixed gas obtained by mixing phosphine gas and hydrogen gas is introduced into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 1%, the gas flow rate of the second mixed gas is 0.1 L / min, and the second mixed gas is stopped after the vapor deposition reaction for 5 minutes; and step 3) and step 4) are alternately deposited 5 times in sequence; and

[0207] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0208] Comparative Example 1

[0209] The negative electrode active particles 100 of this comparative example are prepared by the following steps:

[0210] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0211] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0212] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 20 hours; and

[0213] 4) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0214] Comparative Example 2

[0215] The negative electrode active particles 100 of this comparative example are prepared by the following steps:

[0216] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0217] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0218] 3) introducing a first mixed gas obtained by mixing silane gas and argon gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, and the first mixed gas is stopped after the vapor deposition reaction is carried out for 20 hours;

[0219] 4) a second mixed gas formed by mixing phosphine gas and hydrogen gas is introduced into the reaction chamber, wherein the volume fraction of phosphine gas in the second mixed gas is 1%, the gas flow rate of the second mixed gas is 0.1 L / min, and the second mixed gas is stopped after the vapor deposition reaction is carried out for 200 minutes; and

[0220] 5) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0221] Comparative Example 3

[0222] The negative electrode active particles 100 of this comparative example are prepared by the following steps:

[0223] 1) Providing a carbon skeleton 10, wherein the carbon skeleton 10 has a plurality of pores 11, and the specific surface area of ​​the carbon skeleton 10 is 1624 m 2 / g.

[0224] 2) placing the carbon skeleton 10 into a reaction chamber, introducing argon gas, and heating the chamber to 580° C.;

[0225] 3) simultaneously passing a first mixed gas formed by mixing silane gas with argon gas and a second mixed gas formed by mixing phosphine gas with hydrogen gas into the reaction chamber, wherein the volume fraction of silane in the first mixed gas is 30%, the gas flow rate of the first mixed gas is 0.1 L / min, the volume fraction of phosphine gas in the second mixed gas is 1%, and the gas flow rate of the second mixed gas is 0.1 L / min, and the first mixed gas and the second mixed gas are stopped after the deposition reaction is carried out for 20 hours;

[0226] 4) The temperature is heated to 750° C., and acetylene gas is introduced for deposition for 2 hours to form a carbon coating layer 70 on the surface of the carbon skeleton 10 to obtain negative electrode active particles 100.

[0227] The negative electrode active particles 100 obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were tested:

[0228] 1) Conductivity test: 1000.5 g of negative electrode active particles were weighed and placed in a test mold. A pressure of 162 MPa was applied to the test mold. A two-probe method was used to place the terminals at both ends of the sample. An AC voltage signal was input to collect the current at both ends of the sample, thereby obtaining the sample conductivity.

[0229] 2) Size of the silicon-phosphorus particles 30: A scanning transmission electron microscope (STEM) is used to obtain an electron microscope image (ie, HAADF image) and calculate the particle size (statistical average) of the silicon-phosphorus particles 30.

[0230] 3) Preparation of button half-cell: negative electrode active particles 100 are mixed with conductive carbon black, carbon nanotubes and polyacrylic acid in a mass ratio of 82:8:2:8 to form a slurry, the slurry is coated on a copper foil, vacuum dried and roll-pressed to obtain a negative electrode sheet, and the negative electrode sheet is assembled into a button half-cell with a lithium sheet as the counter electrode.

[0231] 4) The button half-cell was subjected to capacity division and cycle tests: discharged at a discharge rate of 0.1C to 5mV, allowed to stand for 5min, then discharged at a discharge rate of 0.05C to 5mV, allowed to stand for 5min, then discharged at a discharge rate of 0.02C to 5mV, allowed to stand for 10min, and charged at 0.1C to 1.5V. The cycle was repeated 100 times, and the cycle capacity retention rate after 100 cycles was calculated.

[0232] The measurement results of each embodiment and comparative example are shown in Table 1 below.

[0233] Table 1 Measurement results of negative electrode active particles 100 of various embodiments and comparative examples

[0234]

[0235]

[0236] It can be seen from the test results of Examples 1 to 6 that the negative electrode active particles 100 prepared by the method of the present application have a higher electrical conductivity, all of which are above 5.7 S / cm. The particle size of the silicon phosphorus particles 30 of the negative electrode active particles 100 is smaller, all below 2 nm, and has a higher specific capacity and a higher cycle capacity retention rate (greater than or equal to 88.7%).

[0237] It can be seen from the test data of Example 1 and Example 2 that the phosphorus deposition time of Example 1 accounts for a longer proportion of the total deposition time. Therefore, the phosphorus content in the negative electrode active particles 100 of Example 1 is greater than the phosphorus content in the negative electrode active particles 100 of Example 2. More phosphorus can provide more free electrons and better increase the carrier concentration in the silicon phase, so that the negative electrode active particles 100 of Example 1 have higher conductivity than the negative electrode active particles 100 of Example 2. In addition, the number of alternations in Example 1 is greater, which can better block the growth of the silicon phase, thereby making the particle size of the silicon phosphorus particles 30 of Example 1 smaller, which can better prevent Li from being inserted during lithium insertion. 15 The formation of the Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particles 100. Therefore, the negative electrode active particles 100 of Example 1 have a higher cycle capacity retention rate than the negative electrode active particles 100 of Example 2.

[0238] It can be seen from the test data of Example 1 and Example 3 that, compared with Example 1, when phosphorus is deposited in Example 3, the concentration of phosphine increases, so Example 3 has a higher phosphorus content. The higher phosphorus content can provide more free electrons and better increase the carrier concentration in the silicon phase, so that the negative electrode active particles 100 of Example 3 have a higher conductivity than the negative electrode active particles 100 of Example 1. In addition, a higher phosphorus content can better block the growth of the silicon phase, so that the particle size of the silicon phosphorus particles 30 of the negative electrode active particles 100 of Example 3 is smaller than that of Example 1, which can better prevent Li from being inserted into the negative electrode active particles 100. 15 The formation of Si4 crystal phase improves the cycle capacity retention rate of the negative electrode active particles 100, so the negative electrode active particles 100 of Example 3 have a higher cycle capacity retention rate than the negative electrode active particles 100 of Example 1. However, the silicon content of Example 3 is reduced, so the specific capacity is slightly reduced.

[0239] It can be seen from the test data of Examples 1 and 4 that the total amount of phosphorus deposited in Example 4 is less than that in Example 1. Therefore, compared with Example 1, the conductivity of the negative electrode active particles 100 in Example 4 is reduced and the cycle capacity retention rate is slightly reduced.

[0240] It can be seen from the test data of Example 1 and Example 5 that compared with Example 1, the total deposition amount of phosphorus in Example 5 is reduced. Therefore, compared with Example 1, the conductivity of the negative electrode active particles 100 in Example 5 is reduced; in addition, the silicon phosphorus particles 30 become larger, thereby significantly reducing the cycle capacity retention rate of the negative electrode active particles 100.

[0241] It can be seen from the test data of Example 1 and Example 6 that, compared with Example 1, the total amount of phosphorus deposited in Example 5 is reduced, so the conductivity of the negative electrode active particles 100 of Example 6 is reduced; in addition, the silicon deposition time is longer, so the particle size of the obtained silicon phosphorus particles 30 is larger; the reduction in conductivity and the increase in the particle size of the silicon phosphorus particles 30 reduce the cycle capacity retention rate of the negative electrode active particles 100 of Example 6. Furthermore, the specific surface area of ​​the carbon skeleton 10 of Example 6 is reduced, indicating that the amount of pores 11 of the carbon skeleton 10 is reduced, and the amount of silicon phosphorus particles 30 that can be deposited is reduced, so that the specific capacity of Example 6 is greatly reduced.

[0242] From the test data of Example 1 and Comparative Example 1, it can be seen that in Comparative Example 1, there is no phosphorus deposition, and only silicon deposition is performed. The conductivity of the silicon-carbon composite material is greatly reduced, the particle size of the silicon particles is greatly increased, and the cycle capacity retention rate of the obtained negative electrode active particles 100 is also greatly reduced.

[0243] From the test data of Example 1 and Comparative Example 2, it can be seen that compared with 40 times of alternate silicon deposition and phosphorus deposition in Example 1, Comparative Example 2 only performs one silicon deposition and one phosphorus deposition. Although the total silicon deposition time of Example 1 and Comparative Example 1 is the same, compared with Example 1, the conductivity of the negative electrode active particles 100 obtained in Comparative Example 2 is greatly reduced, the size of the silicon phosphorus particles 30 is increased, and the specific capacity and cycle capacity retention rate of the negative electrode active particles 100 are reduced. This shows that the negative electrode active particles 100 obtained by multiple alternating depositions have higher conductivity, smaller silicon phosphorus particles 30 size, higher specific capacity and higher cycle capacity retention rate than those obtained by one alternating deposition.

[0244] In Example 1, silicon deposition and phosphorus deposition were performed alternately for 40 times, and in Comparative Example 3, silicon deposition and phosphorus deposition were performed simultaneously. In Example 1, silicon deposition and phosphorus deposition were performed alternately, and phosphorus source gas was introduced when silicon was deposited to silicon particles of 1 nm. The phosphorus source gas began to decompose and deposit on the surface of the silicon particles to form phosphorus particles 50, and a portion of phosphorus atoms would penetrate into the silicon particles during this heating process to form silicon-phosphorus particles 30. The phosphorus particles 50 formed on the surface would prevent the subsequent silicon particles from continuing to grow. Silicon source gas was introduced again, and the silicon source gas was stopped when a silicon particle size of 1 nm (for example) was formed, and the phosphorus source gas was replaced to form phosphorus particles 50 on the surface of the silicon particles to prevent the continued deposition of silicon. In this way, the size of the silicon-phosphorus particles 30 finally formed in Example 1 would be controlled at 1 nm. In Comparative Example 3, the silicon source and phosphorus source are introduced simultaneously, so that the silicon source gas and the phosphorus source gas enter the multiple pores 11 of the carbon skeleton 10 in a mixed state and begin to deposit on the pore walls. The simultaneous deposition of the mixed gas will cause the silicon atoms and phosphorus atoms to be deposited simultaneously, and the phosphorus atoms are dispersed between the silicon atoms to form silicon-phosphorus particles 30. The silicon-phosphorus particles 30 will gradually increase as the deposition process proceeds until they grow to the size of each pore size. For example, if the pore size is 3nm, 3nm silicon-phosphorus particles 30 will eventually be formed. As a result, the negative electrode active particles 100 obtained by alternately depositing silicon and phosphorus in Example 1 have higher conductivity, the size of the silicon-phosphorus particles 30 in the negative electrode active particles 100 is smaller, the negative electrode active particles 100 have a higher specific capacity, and the cycle capacity retention rate is higher.

[0245] See also Fig. 9 The embodiment of the present application also provides a negative electrode plate 400, which includes a negative electrode collector 410 and a negative electrode active layer 430, wherein the negative electrode active layer 430 is arranged on the surface of the negative electrode collector 410, and the negative electrode active layer 430 includes the negative electrode active particles 100 described in the embodiment of the present application or the negative electrode active particles 100 prepared by the preparation method of the negative electrode active particles 100 described in the embodiment of the present application.

[0246] Optionally, the negative electrode current collector 410 may be, but is not limited to, a copper sheet.

[0247] Optionally, the negative electrode active layer 430 further includes a conductive agent and a binder. It can be understood that the negative electrode active particles 100, the conductive agent and the binder are uniformly dispersed.

[0248] Optionally, the conductive agent may be, but is not limited to, conductive carbon black (SP for short) or carbon nanotube (CNT for short).

[0249] Optionally, the binder may be, but is not limited to, polyacrylic acid (PAA for short).

[0250] Optionally, the negative electrode active layer 430 may be disposed on one surface or multiple surfaces of the negative electrode current collector 410 .

[0251] See also Fig.10 and Fig.11 The embodiment of the present application also provides a battery 500, which includes: an electrolyte, a positive electrode plate 510, a separator 530 and a negative electrode plate 400 of the embodiment of the present application, wherein the positive electrode plate 510 is at least partially immersed in the electrolyte; the separator 530 is located on one side of the positive electrode plate 510 and is at least partially immersed in the electrolyte; the negative electrode plate 400 is arranged on the side of the separator 530 away from the positive electrode plate 510 and is at least partially immersed in the electrolyte.

[0252] It can be understood that the positive electrode sheet 510 , the separator 530 , and the negative electrode sheet 400 are stacked in sequence.

[0253] The battery 500 of the embodiment of the present application may be, but is not limited to, a lithium ion secondary battery, a lithium ion primary battery, a lithium sulfur battery, a sodium lithium ion battery, a sodium ion battery or a magnesium ion battery.

[0254] Please also see Fig.12 Optionally, the positive electrode plate 510 includes a positive electrode current collector 511 and a positive electrode active layer 513 covering the surface of the positive electrode current collector 511 .

[0255] The positive electrode current collector 511 may be, but is not limited to, an aluminum sheet.

[0256] Optionally, the electrolyte may include but is not limited to lithium hexafluorophosphate (LiPF6) and the like.

[0257] Optionally, the diaphragm 530 may be, but is not limited to, at least one of a polypropylene film (PP) and a polyethylene film (PE).

[0258] In some embodiments, the battery 500 further includes a housing 550 and an end cap assembly 570, wherein the housing 550 and the end cap assembly 570 enclose a receiving space, and the receiving space is used to receive the electrolyte, the positive electrode sheet 510, the separator 530, and the negative electrode sheet 400. The end cap assembly 570 includes a positive electrode column and a negative electrode column, wherein the positive electrode column is electrically connected to the positive electrode sheet 510, and the negative electrode column is electrically connected to the negative electrode sheet 400, and the positive electrode column and the negative electrode column are used to electrically connect the battery 500 to an electrical device or other battery 500.

[0259] It can be understood that the battery 500 described in this embodiment is only a form of the battery 500 used by the negative electrode plate 400, and should not be understood as a limitation on the battery 500 provided in this application, nor should it be understood as a limitation on the negative electrode plate 400 provided in each embodiment of this application.

[0260] See also Fig.13 and Fig.14 The embodiment of the present application further provides an electronic device 600, which includes a device body 610 and the battery 500 described in the embodiment of the present application, and the battery 500 is used to power the device body 610.

[0261] The electronic device 600 of the embodiment of the present application may be, but is not limited to, a portable electronic device 600 such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart toy, a smart glasses, a smart bracelet, a smart watch, an e-reader, a game console, a toy, or the like.

[0262] For a detailed description of the battery 500 , please refer to the description of the corresponding part of the above embodiment, which will not be repeated here.

[0263] It can be understood that the electronic device 600 described in this embodiment is merely a form of electronic device 600 used by the battery 500, and should not be understood as a limitation on the electronic device 600 provided in this application, nor should it be understood as a limitation on the battery 500 provided in each embodiment of this application.

[0264] Optionally, the device body 610 of the embodiment of the present application further includes a display screen 611, a middle frame 613 and a shell 615. The shell 615 is arranged opposite to the display screen 611, the middle frame 613 is located between the display screen 611 and the shell 615, and the side wall of the middle frame 613 is exposed to the display screen 611 and the shell 615, the middle frame 613 and the shell 615 enclose a housing space, the housing space is used to accommodate the battery 500, the display screen 611 is electrically connected to the battery 500, and the battery 500 supplies power to the display screen 611.

[0265] Optionally, the display screen 611 may be, but is not limited to, one or more of a liquid crystal display screen, a light emitting diode display screen (LED display screen), a micro light emitting diode display screen (Micro LED display screen), a sub-millimeter light emitting diode display screen (Mini LED display screen), an organic light emitting diode display screen (OLED display screen), etc.

[0266] Please also see Fig.15 Optionally, the device body 610 of the present application further includes a processor 617 and a memory 616. The processor 617 and the memory 616 are arranged in the accommodation space, and the processor 617 is electrically connected to the battery 500, the display screen 611 and the memory 616 respectively. The processor 617 is used to control the display screen 611 to display, and the memory 616 is used to store the program code required for the operation of the processor 617, the program code required to control the display screen 611, the display content of the display screen 611, etc.

[0267] Optionally, the processor 617 includes one or more general-purpose processors, wherein the general-purpose processor can be any type of device capable of processing electronic instructions, including a central processing unit (CPU), a microprocessor, a microcontroller, a main processor, a controller, and an ASIC, etc. The processor 617 is used to execute various types of digital storage instructions, such as software or firmware programs stored in the memory 616, which enables the computing device to provide a wide variety of services.

[0268] Optionally, the memory 616 may include a volatile memory (Volatile Memory), such as a random access memory (Random Access Memory, RAM); the memory 616 may also include a non-volatile memory (NVM), such as a read-only memory (Read-Only Memory, ROM), a flash memory (Flash Memory, FM), a hard disk drive (Hard Disk Drive, HDD) or a solid-state drive (SSD). The memory 616 may also include a combination of the above-mentioned types of memory 616.

[0269] In some embodiments, the device body 610 of the embodiment of the present application further includes a camera module 618, which is disposed in the accommodation space. The camera module 618 is electrically connected to the processor 617 and the battery 500, respectively, and is used to shoot under the control of the processor 617, and the battery 500 also supplies power to the camera module 618.

[0270] Optionally, the housing 615 has a light-transmitting portion 6151, and the camera module 618 can shoot through the light-transmitting portion 6151 on the housing 615, that is, the camera module 618 in this embodiment is a rear camera module 618. It can be understood that in other embodiments, the light-transmitting portion 6151 can be set on the display screen 611, that is, the camera module 618 is a front camera module 618. In the schematic diagram of this embodiment, the light-transmitting portion 6151 is illustrated as an opening. In other embodiments, the light-transmitting portion 6151 may not be an opening, but a light-transmitting material, such as plastic, glass, etc.

[0271] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0272] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. A negative electrode active particle, characterized in that: include: A carbon skeleton having a plurality of pores; silicon-phosphorus particles, the silicon-phosphorus particles being located in the plurality of pores; as well as Phosphorus particles are located in the plurality of pores.

2. The negative electrode active particle according to claim 1, characterized in that: In the negative electrode active particles, the mass of phosphorus element is 0.1% to 25% of the mass of silicon element.

3. The negative electrode active particle according to claim 1, characterized in that: In the negative electrode active particles, the mass of phosphorus element is 0.5% to 5% of the mass of silicon element.

4. The negative electrode active particle according to claim 1, characterized in that: The particle size D1 of the silicon-phosphorus particles is in the range of 0.2 nm ≤ D1 ≤ 2 nm.

5. The negative electrode active particle according to claim 1, characterized in that: The particle size D2 of the phosphorus particles is in the range of 0.1 nm ≤ D2 ≤ 1.5 nm.

6. The negative electrode active particle according to claim 1, characterized in that: The negative electrode active particles further include a carbon coating layer, and the carbon coating layer is wrapped around the periphery of the carbon skeleton.

7. The negative electrode active particle according to claim 6, characterized in that: In the negative electrode active particles, the mass ratio of the silicon element to the carbon element is 1:9 to 9:

1.

8. The negative electrode active particle according to claim 6, characterized in that: In the negative electrode active particles, the mass ratio of the silicon element to the carbon element is 3:7 to 7:

3.

9. The negative electrode active particle according to claim 6, characterized in that: The specific surface area S of the negative electrode active particles is in the range of: 0.15m 2 / g≤S≤30m 2 / g.

10. The negative electrode active particle according to claim 6, characterized in that: The range of the median particle size D50 of the negative electrode active particles is: 1 μm≤D50≤20 μm.

11. The negative electrode active particle according to any one of claims 6 to 10, characterized in that: The range of the thickness L of the carbon coating layer is: 1nm≤L≤2000nm.

12. A method for preparing negative electrode active particles, characterized in that: include: providing a carbon skeleton having a plurality of pores; and Silicon source gas and phosphorus source gas are alternately introduced into the carbon skeleton to deposit silicon-phosphorus particles and phosphorus particles in the plurality of pores to obtain negative electrode active particles, wherein the negative electrode active particles include a carbon skeleton, silicon-phosphorus particles and phosphorus particles.

13. The method for preparing negative electrode active particles according to claim 12, characterized in that: The step of alternately introducing silicon source gas and phosphorus source gas into the carbon skeleton comprises the following steps which are performed alternately multiple times: A silicon source gas is introduced to perform a first vapor deposition at a first temperature T1 of 450° C. ≤ T1 ≤ 700° C.; as well as A phosphorus source gas is introduced and a second vapor deposition is performed at a second temperature T2 of 300° C. ≤ T2 ≤ 900° C.

14. The method for preparing negative electrode active particles according to claim 13, characterized in that: The silicon source gas is introduced, and the first vapor deposition is performed at a first temperature T1 of 450° C. ≤ T1 ≤ 700° C., including: A first mixed gas formed by mixing the silicon source gas with a first carrier gas is introduced into the carbon skeleton to perform a first vapor deposition at a first temperature T1 of 450°C ≤ T1 ≤ 700°C, wherein the volume fraction of the silicon source gas in the first mixed gas is 1% to 70%.

15. The method for preparing negative electrode active particles according to claim 13, characterized in that: The phosphorus source gas is introduced, and the second vapor deposition is performed at a second temperature T2 of 300° C. ≤ T2 ≤ 900° C., including: A second mixed gas formed by mixing the phosphorus source gas with a second carrier gas is introduced into the carbon skeleton to perform a second vapor deposition at a second temperature T2 of 300°C ≤ T2 ≤ 900°C, wherein the volume fraction of the phosphorus source gas in the second mixed gas is 0.1% to 70%.

16. The method for preparing negative electrode active particles according to claim 13, characterized in that: The total volume of the silicon source gas introduced alternately for multiple times is V1, and the total volume of the phosphorus source gas introduced alternately for multiple times is V2, wherein 3≤V1 / V2≤999.

17. The method for preparing negative electrode active particles according to any one of claims 13 to 16, characterized in that: The time for each first vapor deposition is t1, and the time for each second vapor deposition is t2, wherein 1≤t1 / t2≤1200.

18. A negative electrode plate, characterized in that: include: Anode current collector; as well as A negative electrode active layer, wherein the negative electrode active layer is disposed on the surface of the negative electrode current collector, and the negative electrode active layer comprises the negative electrode active particles according to any one of claims 1 to 11 or the negative electrode active particles prepared by the method for preparing the negative electrode active particles according to any one of claims 12 to 17.

19. A battery, characterized in that: include: Electrolyte; A positive electrode sheet, wherein the positive electrode sheet is at least partially immersed in the electrolyte; a diaphragm, the diaphragm being located on one side of the positive electrode plate and at least partially immersed in the electrolyte, and The negative electrode plate as described in claim 18 is arranged on the side of the diaphragm away from the positive electrode plate and is at least partially immersed in the electrolyte.

20. An electronic device, characterized in that: include: Equipment body; as well as The battery as described in claim 19 is used to power the device body.

Citation Information

Cited By

  • Preparation method of phosphorus / silicon composite negative electrode material

    CN120796938A